Effect of Feeding Formaldehyde Treated Rapeseed Meal on Metabolic Profile of Surti Buffalo Heifers - Sorathiya, Kalpesh K.; Chaubey, Mahipal; Jadhav, Mahesh D.; Vahora, Safi G.; Patel, Vipul R.; Tabhani, Prakash M.; Lunagariya, Pravin M. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Present experiment was conducted on Surti buffalo heifers to compare the graded level (0%, 0.25%, 0.50%, and 1% CP) of formaldehyde (HCHO)-treated rapeseed meal (RSM) in compounded concentrate mixture (CCM) on various metabolic indices. A total of twenty Surti buffalo heifers (16-18 months old; 164.68±5.43 kg) were divided into 4 homogeneous groups of 5 individuals each. The CCM was formulated using formaldehyde-treated rapeseed meal (@ 0%, 0.25%, 0.50%, or 1% HCHO-treated RSM CP), damaged wheat, corn grit, cottonseed extract, rice polish (fine), deoiled rice bran, rice flake bran, molasses, urea, calcite powder and common salt. FT-0 group was fed with CCM having untreated RSM, while FT-25, FT-50 and FT-100 groups were fed CCM having 0.25 %, 0.5 % and 1% CP from HCHO treated rapeseed meal. Results revealed non-significant differences in the serum total protein, albumin, globulin, cholesterol, albumin: globulin ratio and aspartate transaminase and alanine transaminase activities among different groups of heifers. However, serum urea concentration decreased (p<0.01) due to increased formaldehyde treated RSM (0, 0.25, 0.5 and 1%) in the CCM. Serum T3 level was found elevated (p<0.05) in the FT-50 and FT-100 groups, which revealed that formaldehyde treatment (@ 0.5 % and 1.0 %) had effectively destroyed the glucosinolate in rapeseed meal. Decreased serum urea and increased T3 levels of FT-50 and FT-100 groups indicated the effectiveness of formaldehyde treatment to protect the rapeseed meal without altering other blood metabolites.